Classification of Uremic Toxins and Their Role in Kidney Failure - Mitchell H. Rosner; Thiago Reis; Faeq Husain‐Syed; Raymond Vanholder; Colin A. Hutchison; Peter Stenvinkel; Peter J. Blankestijn; Mario Cozzolino; Laurent Juillard; Kianoush Kashani; Manish Kaushik; Hideki Kawanishi; et al. (2021)
Advances in our understanding of uremic retention solutes, and improvements in hemodialysis membranes and other techniques designed to remove uremic retention solutes, offer opportunities to readdress the definition and classification of uremic toxins. A consensus conference was held to develop recommendations for an updated definition and classification scheme on the basis of a holistic approach that incorporates physicochemical characteristics and dialytic removal patterns of uremic retention solutes and their linkage to clinical symptoms and outcomes. The major focus is on the removal of uremic retention solutes by hemodialysis. The identification of representative biomarkers for different classes of uremic retention solutes and their correlation to clinical symptoms and outcomes may facilitate personalized and targeted dialysis prescriptions to improve quality of life, morbidity, and mortality. Recommendations for areas of future research were also formulated, aimed at improving understanding of uremic solutes and improving outcomes in patients with CKD.